TOMATO SUPPLY CHAIN ANALYSIS IN FARMERS PUNCAK JAYA SINDANGJAYA VILLAGE, MANGUNJAYA DISTRICT, PANGANDARAN REGENCY - Kurnia, Aceng; Setia, Budi; Yusuf, Muhamad Nurdin (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2023)
The research was carried out with the aim of knowing Tomato supply chain efficiency in Sindangjaya Village, Mangunjaya District, Pangandaran Regency. The sample of tomato farmers was determined by census, while the marketing actors involved in marketing tomatoes were determined using snowball sampling, namely by tracing the marketing flow of the tomatoes from farmers to consumers. The results showed The total marketing margin of tomatoes is IDR 2,600 per kg with a total profit of IDR 850 per kg and a total cost of IDR 1,750 per kg. The profit share value is 61.96% while the cost share value is 35.87%. The share of the price received by farmers (farmer share) is 43.48% so that the tomato supply chain in Sindangjaya Village, Mangunjaya District, Pangandaran Regency is categorized as inefficient because the percentage of Pf (Producer Share) is 70%..Keywords: tomato farming, supply chain